Limiting deforestation involves complex tradeoffs: Results from a global land-use model - Mishra, Abhijeet; Jones, Eleanor (International Food Policy Research Institute, 2024)
Forests are massive carbon sinks and biodiversity havens. The world’s forests store about 861 gigatons of carbon, 42% in live biomass and 44% in soil. Yet forest areas have been disappearing at an alarming rate: Globally, they have shrunk by 20% over the past 100 years, mostly due to expansion of agricultural lands. Given the urgency of reducing global CO2 emissions, world leaders at the 2021 COP26 Global Climate Conference in Glasgow made a non-binding declaration to halt and reverse forest loss and land degradation by 2030. This pledge, endorsed by 145 countries covering 91% of the world’s forests, was hailed as a significant step toward stopping global deforestation.